Interpersonal Meaning in “Greta Thunberg’s Speech” at The United Nations Climate Action Summit 2019 - Vina Uctuvia; Daviq Rizal (ELLITE, 2022)
The objectives of this research were to explain the interpersonal meaning, to describe the dominant mood system, and to describe the pedagogical implications realized in Greta Thunberg’s speech that deliver at the UN Climate Action Summit 2019. The design of this research is qualitative that used descriptive qualitative approach. To analyze the data, the researchers employ SFL approach by using mood analysis as a tool to analyze the data. The data were obtained from speech transcript of Greta Thunberg. The data also triangulated by interviewing English Education Department student and a postgraduate student who has conducted similar research. The researcher found two kinds of mood in the speech, they are; declarative (89.47%) and exclamative (10.52%). Based on the percentage of the mood found in the speech, Thunberg try to give any information about what world leaders responsibilities for climate changing to the audience by using declarative mood and also, she delivered her emotion and strong feeling through exclamative mood. The implication of this study hopefully can provide method and information about how to conduct research related to interpersonal meaning analysis. Keywords: Greta Thunberg’s Speech, Interpersonal Meaning, SFL, Mood Analysis